Defects and diffusion in semiconductors. an annual retrospective - Fisher, D. J. (Diffusion and defect data. Defect and diffusion forum ;, 2008)
This eleventh volume in the series covering the latest results in the field includes abstracts of papers which have appeared since the publication of Annual Retrospective X (Volume 272). As well as the 295 metals abstracts, the issue includes - in line with the new editorial policy of including original papers on all of the major material groups: ""Structural and Electron-Hopping Studies of Pr- and Nd-Substituted La2/3Ba1/3MnO3 Manganites"" (H. Abdullah and S.A. Halim), ""Recrystallization Annealing of Cold-Rolled 9Cr-1Mo Ferritic Steel Containing Silicon"" (M.N. Mungole, M. Surender, R. Balasubram